DIETARY PHOSPHOROUS INTAKE AMONG HAEMODIALYSIS PATIENTS IN RELATION TO DOSAGE OF PHOSPHATE BINDERS AND HYPERPHOSPHATEMIA. - Camilla Cameron RD; Agneta Andersson; Gerd Faxén Irving (The Korean Society of Nephrology, 2012)
Hyperphosphatemia in haemodialysis (HD) patients is associated with mineral and bone disorder and increased cardiovascular disease. Despite dietary restriction of phosphorous (P), improved dialysis therapy and phosphate binders (PB), hyperphosphatemia remains a serious problem among the dialysis population. A sub-optimal relationship between the actual dietary intake of P and the intake of PB's may be one explanation. The aim of the present study was to investigate the dietary P intake in a group of HD patients in relation to the taken dosage of PB, and to establish what, if any, relationship exists with the patients' plasma phosphate level. Self-reported intake of P, assessed by three-day estimated food record, and intake of PB was analysed in thirty-one adult (age 61.8±12.9 years) HD patients (17 men, 14 women), who were divided into two groups according to their plasma P levels. The mean dietary P intake among all patients was 1270±420 mg/d with a mean day-to-day variation of 390±310 mg. The P intake in one single meal ranged from <10 mg to 1430 mg, average 256±200 mg. The variation of dosing regimens of PB among the patients was large (1-4 to 12-16 per day), although each patient's regimen was fixed and in most cases was 3 times daily. No significant differences regarding dietary P intake (p=0.51) nor PB's (p=0.41) between patients with high (>1.6 mmol/l) and low (<1.6 mmol/L) plasma P levels were observed. In conclusion, the findings show a notable individual day-to-day and meal-to-meal variation in dietary P intake and in contradiction, the same individual dosing regimen of PB. Strangely, no significant difference in the dietary P intake or intake of PBs between HD patients with high or low plasma P level was found. The question of whether a PB intake better tailored to the meal and day variation in P intake could prevent hyperphosphatemia will need to be evaluated in further studies.